2014
DOI: 10.1155/2014/175827
|View full text |Cite
|
Sign up to set email alerts
|

Composition, Repellent, and Insecticidal Activities of Two South American Plants against the Stored Grain Pests Tribolium castaneum and Tribolium confusum (Coleoptera: Tenebrionidae)

Abstract: As part of a screening program to evaluate the biological activity of indigenous plants, we report the composition and the bioactivity of essential oils (EOs) extracted from Té de Burro Aloysia polystachya [(Griseb.) Moldenke] and Lemon Verbena Aloysia citriodora [Palau] against two of the most widespread secondary pests of stored products, the red flour beetle Tribolium castaneum [Herbst] and the confused flour beetle Tribolium confusum [Jacqueline du Val]. Analysis by gas chromatography-mass spectrometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…EOs have shown toxic, repellent and antifeedant effects on stored product insects (Isman, 2006;Regnault-Roger et al, 2012, 1997 Fabricius, Sitophilus oryzae L. and Sitophilus zeamais Motsch. (Benzi et al, 2014(Benzi et al, , 2009Papachristos et al, 2004;Singh et al, 2012;Stefanazzi, et al, 2011). Only limited efforts have focused on Lepidopteran pests such as Sitotroga cerealella Olivier, Corcyra cephalonica Stainton and P. interpunctella.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…EOs have shown toxic, repellent and antifeedant effects on stored product insects (Isman, 2006;Regnault-Roger et al, 2012, 1997 Fabricius, Sitophilus oryzae L. and Sitophilus zeamais Motsch. (Benzi et al, 2014(Benzi et al, , 2009Papachristos et al, 2004;Singh et al, 2012;Stefanazzi, et al, 2011). Only limited efforts have focused on Lepidopteran pests such as Sitotroga cerealella Olivier, Corcyra cephalonica Stainton and P. interpunctella.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The LC 50 values of L. citriodora and L. polystachya essential oils against N. viridula were 29.9 and 13.5 mg/l 24 h after treatment, respectively (González et al, 2010). In the same work, L. citriodora and L. polystachya essential oils also exhibited significant fumigant toxicity against T. confusum with LC 50 values of 5.53 and 5.92 mg/l but there was not significant toxicity on the adults of T. castaneum (Benzi et al, 2014). In the other study, Khani et al (2012) revealed that L. citriodora essential oil, with citral (11.3%), limonene (10.6%), and neral (7.9%) as main components, had significant fumigant toxicity on the adults of cowpea weevil (Callosobruchus maculatus (F.)) and the confused flour beetle (Tribolium confusum Jacquelin du Val).…”
Section: Resultsmentioning
confidence: 76%
“…aegypti, Aedes albopictus (Skuse) (Diptera: Culicidae), and C. quinquefasciatus. They found an LC 50 of 32.5, 31.8, and 31.5 mg EO L −1 of water after 24 h. The toxicity by contact of the A. citrodora EO (LD 50 = 13.8 µg EO insect −1 after 72 h) was also demonstrated against adults of the storedproduct pest Tribolium castaneum Herbst (Coleoptera: Tenebrionidae) by Benzi et al [58].…”
Section: Discussionmentioning
confidence: 89%